Differences in DNA Purity Test Using UV-Vis Spectrophotometer and Nanodrop Spectrophotometer in Type 2 Diabetes Mellitus Patients: Perbedaan Uji Kemurnian DNA Menggunakan Spektrofotometer UV-Vis dan Spektrofotometer Nanodrop pada Pasien Diabetes Melitus Tipe 2 - Dewanata, Pandu Aji; Mushlih, Miftahul (Universitas Muhammadiyah Sidoarjo, 2021)
DNA quality test is one of the basic techniques in Molecular Biology which aims to determine the presence or absence of protein and RNA contamination. DNA quantity test can be done using a spectrophotometer. Spectrophotometer is a tool used to measure the concentration of a compound based on its ability to absorb light. The purpose of this study was to determine differences in DNA purity as measured by UV-Vis Spectrophotometer and Nanodrop Spectrophotometer. The method used in this research is descriptive exploratory with purposive sampling technique. The number of samples used is 15 samples. The results of this study are that there are differences in the concentration and purity of DNA from quantitative tests with UV-Vis spectrophotometers and Nanodrops obtained based on statistical tests using the T Dependent Test. The result of this research is that in measuring DNA purity there is a difference in DNA purity because the results of Sig (2-Tailed) use 0.001 or below 0.05 (Ha is accepted). And based on statistical tests on DNA concentration measurements, it is known that there are differences in DNA concentrations.